Preparing Rabies Vaccination Data of Veterinary Health Professionals for Analysis and Best Practices for Rabies Vaccination for Animal Handling Personnel - Sungkatavat, Paparwee (My University, 2021)
Rabies is a fatal zoonotic viral disease which occurs in over 150 countries. Rabies is a significant concern in public health, especially for people who are at risk such as rabies laboratory workers, animal health care workers, people who work with animals such as farmers and slaughterhouse workers, and people who live in rabies-endemic countries. However, rabies can be prevented by vaccination before and/or after suspected or proven exposure to the virus. Therefore, it is important to understand rabies vaccination recommendations in people who are at risk. The primary focus of this project was rabies vaccination for animal handling personnel. The first part was to prepare human laboratory data for statistical evaluation and send to the evaluators at University of Washington School of Public Health to use, then summarize the process of preparing data. Next, I created a summary of the best practices for rabies vaccination and booster timing for personnel handling animals, and a poster for educating animal handling staff on rabies control and prevention. These products could be useful for animal handling personnel for rabies prevention.
Keywords: rabies; vaccination